2019
DOI: 10.3390/cells8040338
|View full text |Cite
|
Sign up to set email alerts
|

Microrna-130a Downregulates HCV Replication through an atg5-Dependent Autophagy Pathway

Abstract: We previously identified that miR-130a downregulates HCV replication through two independent pathways: restoration of host immune responses and regulation of pyruvate metabolism. In this study, we further sought to explore host antiviral target genes regulated by miR-130a. We performed a RT² Profiler™ PCR array to identify the host antiviral genes regulated by miR-130a. The putative binding sites between miR-130a and its downregulated genes were predicted by miRanda. miR-130a and predicted target genes were ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…And, miR-130a regulates host antiviral response and HCV replication through targeting ATG5 via the ATG5-dependent autophagy pathway. 146 Bovine viral diarrhea virus (BVDV), the causative agent of bovine viral diarrhea/mucosal disease (BVD/MD), is an important pathogen associated with reproductive, gastrointestinal, and respiratory diseases. Lentivirus-mediated bta-miR-29b overexpression interferes with BVDV replication and viral infection-related autophagy by directly targeting ATG14 and ATG9A in Madin-Darby bovine kidney (MDBK) cells ( Table 5).…”
Section: Mirs Regulate Autophagy In Viral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…And, miR-130a regulates host antiviral response and HCV replication through targeting ATG5 via the ATG5-dependent autophagy pathway. 146 Bovine viral diarrhea virus (BVDV), the causative agent of bovine viral diarrhea/mucosal disease (BVD/MD), is an important pathogen associated with reproductive, gastrointestinal, and respiratory diseases. Lentivirus-mediated bta-miR-29b overexpression interferes with BVDV replication and viral infection-related autophagy by directly targeting ATG14 and ATG9A in Madin-Darby bovine kidney (MDBK) cells ( Table 5).…”
Section: Mirs Regulate Autophagy In Viral Diseasesmentioning
confidence: 99%
“…Molecular assays for detection and accurate quantitation of hepatitis C virus (HCV) RNA have been important for identification and management of the hepatitis C. ATG5, a target gene for miR‐130a, significantly upregulated HCV replication and downregulated interferon‐stimulated gene expression. And, miR‐130a regulates host antiviral response and HCV replication through targeting ATG5 via the ATG5‐dependent autophagy pathway . Bovine viral diarrhea virus (BVDV), the causative agent of bovine viral diarrhea/mucosal disease (BVD/MD), is an important pathogen associated with reproductive, gastrointestinal, and respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, miR-155 is a multifunctional microRNA that has an indispensable capacity in immune responses [ 41 ]. We previously reported that miR-130a regulates HCV and HBV infection through the IFN pathway [ 32 , 42 ]. In the present study, we also found that miR-155 and miR-130a were significantly upregulated in COVID-19 patients when compared to negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the authors identified an actor of HCV maintenance in the autophagy process [21]. Amongst the genes involved in the autophagy process, ATG5, a key regulator of the process, was a target of miR-130a.…”
Section: Micrornas In the Hcv Life Cyclementioning
confidence: 99%
“…The microRNAs involved in the HCV life cycle and their biological significance are reported in Table 1. [9,10] Together with the Argonaute protein (AGO) stabilizes and protects the uncapped viral genome from degradation [11] Interaction between miR-122-miRISC-HCV-RNA results in miR-122 sequestration, preventing its binding with host targets and promoting HCV replication [12] DCAF1 targets miR-122 and negatively regulates HCV IRES-mediated translation [15] miR-125b-5p Controversial Downregulates HuR which promotes HCV replication [24] Inhibits miR-125b-5p decreasing HCV expression at both RNA and protein levels [25] miR-130a inhibition Inhibits the ATG5 protein that upregulates the expression of type I IFN and of molecules involved in innate immune response [20][21][22] HCV replication is inhibited through the reduced production of ATP and other glycolytic intermediates [23] miR-199a-5p enhancement Stimulates pro-survival pathways like PI3K/Akt, Ras/ERK, and Wnt/β-catenin [18] miR-215 enhancement Inactivates NF-κB pathway by inhibiting TRIM22 [17] miR-491 enhancement Low levels of miR-491 reduced the inhibition of PI3K/AKT pathway which is involved in the maintenance of HCV replication [19]…”
Section: Micrornas In the Hcv Life Cyclementioning
confidence: 99%